Shakespeare and biography - Bevington, David M. (Oxford Shakespeare topics, 2010)
Shakespeare and biography is not a new biography of Shakespeare, but a study of what biographers have said about Shakespeare--from the first formal biography in the early 18th century by Nicholas Rowe, to others who have written recent biographical accounts. The emphasis is on what sorts of issues these biographers have found especially interesting, how contemplation of these issues has changed and grown, and the ways those changes reflect new cultural developments in our world as it continues to reinterpret Shakespeare